Weak approximations of Wright-Fisher equation - Mongirdaitė, Gabrielė; Mackevičius, Vigirdas (Lietuvos matematikos rinkinys, 2021)
We construct weak approximations of the Wright-Fisher model and illustrate their accuracy by simulation examples.